Effectiveness of Samapta Unit Precision Pioneer Patrols in the Prevention of the Crime of Theft with Weights in the Jurisdiction of Madiun Police - Putrawan, I Putu Satria Mahotama (Advances in Police Science Research Journal, 2024)
The Indonesian National Police plays a role in maintaining public order, one of which is through preventive measures with the Patroli Perintis Presisi of the Samapta Unit. The high incidence of aggravated theft in Madiun Police Resort indicates the ineffectiveness of the implementation of the Patroli Perintis Presisi in Madiun Police Resort. This study adopts qualitative approach with field research as the type of study. This study aims to describe the implementation of the Patroli Perintis Presisi of the Samapta Unit in preventing aggravated theft and to describe the effectiveness of the Samapta Unit of Madiun Resort in conducting the Patroli Perintis Presisi.